2022
DOI: 10.1101/2022.02.10.479864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective effects of a short transient environmental fluctuation on a natural population

Abstract: Natural populations experience continuous and often transient changes of environmental conditions. These in turn may result in fluctuating selection pressures leading to variable demographic and evolutionary population responses. Rapid adaptation as short-term response to a sudden environmental change has in several cases been attributed to polygenic traits, but the underlying genomic dynamics and architecture are poorly understood. In this study, took advantage of a natural experiment in an insect population … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Most importantly for the diagnosis of adaptive tracking was that phenotypic evolution occurred on the same temporal scale as the environmental change. However, we did not test for a direct link between any environmental parameter and a phenotypic trait, because i) the measured traits are rather highly inclusive fitness components, thus integrating the influence of many lower level traits, ii) transient, short term extreme events were not recorded by the long-term averages, but are known to exert important selective pressure (Pfenninger et al ., 2022). All measured traits have strong links to fitness, which also varied over the monitored period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly for the diagnosis of adaptive tracking was that phenotypic evolution occurred on the same temporal scale as the environmental change. However, we did not test for a direct link between any environmental parameter and a phenotypic trait, because i) the measured traits are rather highly inclusive fitness components, thus integrating the influence of many lower level traits, ii) transient, short term extreme events were not recorded by the long-term averages, but are known to exert important selective pressure (Pfenninger et al ., 2022). All measured traits have strong links to fitness, which also varied over the monitored period.…”
Section: Discussionmentioning
confidence: 99%
“…A short range haplotype structure is a precondition for the observed short distance between haplotypes responding to selection. Since only haplotypes with more than a single SNP were considered, this may even present an underestimate, because ancient selected polymorphisms may very well be completely separated from their background by recombination (Pfenninger et al ., 2022). In some instances, even different parts of the same gene followed different evolutionary trajectories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long before species demographically decline or actually vanish, stressor effects on population fitness manifests on the molecular level: transcription patterns and mutation rates change (Singh et al, 2020). Last but not least, adaptive processes are triggered (Kosakivska et al, 2021) that result in measurable changes of allele frequencies at affected loci throughout the genome (Pfenninger et al, 2022).…”
mentioning
confidence: 99%
“…It is therefore plausible that temporal changes in environmental conditions likewise change the phenotypic optimum, which is then tracked by respective changes in allelic frequency to reach the new equilibrium frequency. Such adaptation from standing genetic variation to track temporally moving phenotypic optima is theoretically possible nearly in real time (Matuszewski et al, 2015) and has recently been shown empirically (Pfenninger et al, 2022). Monitoring the selectively driven changes of the associated genetic variation is therefore the basis of the proposed approach.…”
mentioning
confidence: 99%